A high-pressure isostatic lamination technique to fabricate versatile carbon electrode-based perovskite solar cells - Luke J. Sutherland; Juan Benitez-Rodriguez; Doojin Vak; Shiqin Yan; Narendra Pai; Jacek Jasieniak; Mei Gao; George P. Simon; Hasitha C. Weerasinghe (Communications Materials, 2024)
Abstract Perovskite solar cells (PSCs) with evaporated gold (Au) electrodes have shown great efficiencies, but the maturity of the technology demands low-cost and scalable alternatives to progress towards commercialisation. Carbon electrode-based PSCs (C-PSCs) represent a promising alternative, however, optimising the interface between the hole transport layer (HTL) and the carbon electrode without damaging the underlying functional layers is a persistent challenge. Here, we describe a lamination technique using an isostatic press that can apply exceedingly high pressure to physically form an HTL/carbon interface on par with vacuum-evaporated electrodes, without damaging the device. Research-scale C-PSCs with a power conversion efficiency (PCE) of up to 20.8% are demonstrated along with large-area C-PSCs with PCEs of 19.8% and 16.9% for cell areas of 0.95 cm2 and 5.5 cm2, respectively. The unencapsulated C-PSCs significantly outperform the Au-electrode devices in accelerated operational stability testing (ISOS-L-1), retaining 84% of the initial PCE after 1000 h. Additionally, this versatile technique is also used to fabricate flexible, roll-to-roll printed C-PSCs with efficiencies of up to 15.8%.